PEMBENTUKAN KARAKTER SISWA MELALUI PENGELOLAAN KELAS - Rian Nurizka; Abdul Rahim (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2019)
ABSTRACT: This study aims to determine the formation of student character through classroom management. The extent to which schools implement classroom management in support of the formation of student character. This type of research is a descriptive qualitative research. This research can be classified in the field research category. The subjects of this study are the Principal, Teachers, and Students. Data collection used in this study uses observation, interview, and documentation techniques. Data analysis in this research is data collection, data reduction, data presentation, and drawing conclusions. The results showed that in shaping student character through classroom management consisting of 1) Creation of a conducive classroom physical environment by involving students in class structuring, 2) Management of student learning activities with innovations by applying varied learning models, class as a learning structure applying goodness outside, installing national figures that can be used as learning for students, creating a learning atmosphere created by teachers in the classroom, 3) Application of learning strategies. Implementation of learning strategies by means of student learning resources obtained from the school environment to cultivate love of the environment, discipline and responsibility in terms of completing assignments, honestly not cheating on tests, instilling obedience to religion by always praying at the beginning and end of learning and through religious practice, and care for friends.Keywords: Character, Classroom Management, Principal's leadership